(untitled) (Proceedings of the International Scientific Conference "Social Changes in the Global World", 2020)
The paper addresses the main features of the new Law on Misdemeanours, related to the provision of efficient judicial protection in misdemeanour administrative proceedings and misdemeanour administrative disputes. At the same time, the paper contains a chronology of reforms in misdemeanour legislation and criticism of incompatible legal solutions, illustrated by case law decisions. The main purpose of the paper is to provide detailed explanations of the new key provisions which, as sui generis, redefine the system of sanctions, and for the penalty measurement, a legal lower and upper threshold of the fine is stipulated for individuals and officers in charge respectively, as well as for legal entities, in accordance with the classification provided in the Law on Business Companies. The need for effectiveness of the misdemeanour proceedings has been fulfilled by reforming the pre-trial misdemeanour proceedings, as well as the corrections in order to improve the procedural guarantees. It is in the interest of the research to prove that there should be no legal provisions in the application and enforcement of the law in misdemeanour proceedings before the courts that cause legal uncertainty and illegal consequences. Judicial efficiency is ensured by precise and clear legal norms that guarantee legal certainty and rule of law. By analysing the case law, it is realistic to expect that the new law shall raise the level of misdemeanour justice.